Preparation and Physicochemical Characterisation of Suryaprabha Gulika (International Journal of Ayurveda and Pharma Research, 2022)
Suryaprabha gulika is a Kharaleeya preparation mentioned in the Gulika prakarana of Sahasrayogam indicated for Sula, Swasa, Kasa and Mahajwara. It contains eleven ingredients namely Suddha Parada, Suddha Gandhaka, Suddha Hingu, Amalaki, Harithaki, Vibheethaki, Sunti, Pippali, Maricha, Yavani and Suddha Vatsanabha triturated for 6 hours in Jambeera swarasa. In this paper, the work done on pharmaceutical and analytical aspects of Suryaprabha gulika is detailed. Pharmaceutical study included Sodhana of Parada, Sodhana of Gandhaka, preparation of Kajjali, Sodhana of Hingu, Sodhana of Vatsanabha and the preparation of final product whereas the analytical study included evaluation of organoleptic characters, physico chemical parameters and analysis based on modern instrumentation techniques such as X-ray Fluorescence (XRF), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and particle size analysis.